Peculiarities of vitamin D metabolism in diabetic kidney disease - V.M. Yerokhovych; O.V. Karpenko; I.A. Paliienko; I.V. Dumka; O.A. Rudenko; Iu.I. Komisarenko (Počki)
The analysis of literature revealed the peculiarities of vitamin D metabolism in diabetic kidney damage, as well as its role in the development of renal, metabolic changes, including bone and mineral disorders. Vitamin D, due to its influence on various physiological processes through vitamin D receptors, plays a key role in the regulation of mineral and bone metabolism, the functioning of the immune system and the control of other extraskeletal effects. In patients with diabetic kidney damage, vitamin D deficiency causes impaired hydroxylation and the formation of an active metabolite (1,25(OH)2D3), which leads to the progression of kidney damage, the development of proteinuria and fibrosis. The mechanisms of glucose and vitamin D interaction at the level of the proximal tubules were analyzed, which emphasizes the need for further research to develop therapeutic strategies for correcting vitamin D deficiency in patients with diabetic kidney damage in order to improve their prognosis.